FINANCIAL IMPACT AND RISKS ON STUDENT INVESTMENT DECISIONS - Hanzhely Syabrina Putrie; Yanti Susanti; Shara Salsabila; Nafa Rona Sugesti (International Journal of Economics, Education, Law and Social Sciences (IJEELSC), 2025)
With the advancement of financial technology, university students now have access to a variety of investment instruments. However, investment decisions are influenced not only by potential returns but also by personal financial conditions and perceptions of risk. This study aims to analyze the influence of financial conditions and risk perception on students' investment decisions. A quantitative approach combining descriptive and associative methods was employed. The descriptive approach provides an overview of student investment behavior, while the associative approach examines the relationship between financial condition (X1), risk perception (X2), and investment decisions (Y). Data were collected through questionnaires distributed to student respondents, resulting in a total of 151 samples. These were analyzed using both descriptive and inferential statistics to explore inter-variable relationships. The respondents were drawn from several universities across Indonesia, including both public and private institutions. The majority of respondents—61 students (40.4%)—came from Yatsi Madani University, while the remaining 90 students (59.6%) were from other universities such as Pamulang University, Raharja University, Jakarta State University, Indonesia University, Padjadjaran University, and Bandung Institute of Technology. Based on the results, it can be concluded that in today's digital era, students' investment behaviors and decisions are significantly influenced by both independent variables: financial condition and risk perception